2020
DOI: 10.1136/annrheumdis-2019-216151
|View full text |Cite
|
Sign up to set email alerts
|

Unmet need in rheumatology: reports from the Targeted Therapies meeting 2019

Abstract: ObjectivesTo detail the greatest areas of unmet scientific and clinical needs in rheumatology.MethodsThe 21st annual international Advances in Targeted Therapies meeting brought together more than 100 leading basic scientists and clinical researchers in rheumatology, immunology, epidemiology, molecular biology and other specialties. During the meeting, breakout sessions were convened, consisting of 5 disease-specific groups with 20–30 experts assigned to each group based on expertise. Specific groups included:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 69 publications
0
59
0
1
Order By: Relevance
“…In clinical practice, the assessment of disease activity in SLE is performed by means of disease activity scores Systemic Lupus Erythematosus Disease Activity Index 2000 (SLE-DAI-2K) or additional testing for the complement components 3 and 4 (C3, C4) and anti-dsDNA titers [4]. The search for new markers of SLE activity is ongoing [5,6]. In recent years, there has been a surge of interest in the role of haematological indicators in the assessment of SLE activity.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, the assessment of disease activity in SLE is performed by means of disease activity scores Systemic Lupus Erythematosus Disease Activity Index 2000 (SLE-DAI-2K) or additional testing for the complement components 3 and 4 (C3, C4) and anti-dsDNA titers [4]. The search for new markers of SLE activity is ongoing [5,6]. In recent years, there has been a surge of interest in the role of haematological indicators in the assessment of SLE activity.…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is one of the most common chronic inflammatory autoimmune diseases, mainly targeting synovial tissues, causing progressive joint destruction [1]. The pathogenesis of RA involves several proinflammatory cytokines such as tumor necrosis factor (TNF)-a and interleukin (IL)-6 [2,3]. In patients with RA, the advent of biologic agents that directly inhibit these cytokines has dramatically improved prognosis by deterring joint destruction and functional disabilities [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…These data could have some practical implications, giving the possibility to the rheumatologist to globally assess the disease activity. In fact, like in our group of patients in follow-up and in a condition of good clinical control of the disease activity, estimating the weight of comorbidities on the final score could be important for treatment decisions in T2T strategy, RCTs, and even in routine clinical care [ 18 ]. Moreover, the impact of comorbidities in the assessment of disease activity could also be useful for other practical aspects, such as the adherence of therapy, which is still an unmet need in how it would be predicted and the potential role of co-existent diseases [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some authors found an almost linear increase of PtGA with increasing number of comorbidities per patients, independently of RA disease activity [ 16 , 17 ]. Another condition, frequently co-existent in PsA patients, such as FM, can significantly and negatively influence the achievement of treatment targets, and still represent an unmet need [ 18 ].…”
Section: Introductionmentioning
confidence: 99%